Enhancing Oral Bioavailability of Isotretinoin by Using Solid Lipid Nanoparticles (SLNs) - Ghangas, Sandeep; Ashok, Praveen Kumar; Hooda, Tanuj (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim: Isotretinoin (ISTN) is a retinoid analogue and known as 13-cis retinoic acid. It is approved for the treatment of Acne vulgaris. Research work was done to improve bioavailability of Isotretinoin by preparing solid lipid nanoparticles and comparison of research formulation with commercially available formulation of Isotretinoin. Central Composite Design (CCD) from response surface methodology was used for test formulation optimisation. Materials and Methods: The test formulation was characterised for particle size, zeta potential, differential scanning calorimetry, drug entrapment efficiency and drug release from Solid Lipid Nanoparticles (SLN). Compritol 888 ATO was used as lipid for the formulation development. Lutrol F68 (poloxamer 188) was used as surfactant. Soy lecithin was also used to stabilize the formulation as it can increase the film forming properties of nanoparticles. Independent parameters, drug lipid ratio (X1) and homogenization speed (X2), were checked at three different levels by using CCD of response surface methodology. Results: p-values (0.003 and 0.000) in ANOVA tables showed the substantial impact of both independent parameters on dependent parameters. Output of central composite design recommended the level of X1 and X2 as 1 for maximum desirability. The optimized formulation was characterized for particle size, zeta potential, differential scanning calorimetry, drug entrapment efficiency and drug release from SLNs. Conclusion: Optimum percentage of the drug to oil phase ratio and higher homogenizer speed significantly impacted the particle size along with drug release.
Keywords: Isotretinoin; Solid Lipid Nanoparticles; Central Composite Design; Response Surface; Methodology; in vitro drug release